2010
DOI: 10.1016/j.aprim.2009.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Adolescentes, situaciones de riesgo y seguridad vial

Abstract: Adolescents in higher grades and living in Andalusia were less road safety conscious. This pattern should be taken into account when designing preventive actions in Road Safety Education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
0
11
0
3
Order By: Relevance
“…The literature so far indicates that this low perception may be associated to family factors related with consumption learned from the environment (Pons & Buelga 2011, Zucker et al, 2009, the normalization of the "soft drug" concept (Lee et al, 2010;Pons, 2008;Pons & Buelga, 2011) disregarded by direct care professionals with drug addicts, or influences by the positive experience of experimental use (Elzo, 2010;Londoño, 2010Moral & Ovejero, 2011; Ruiz-Juan y Ruiz-Risueño, 2011). The research carried out by Meneses et al (2010) on adolescence and risk situations in road safety also confirms differences by gender, reckless driving being more frequent in men than in women. The study by Gil and Romo (2008) on the Andalusian adolescent population also found results similar to those of our study regarding risk behaviors related to road safety, such as consumption of legal and illegal drugs, as well as differences by gender.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The literature so far indicates that this low perception may be associated to family factors related with consumption learned from the environment (Pons & Buelga 2011, Zucker et al, 2009, the normalization of the "soft drug" concept (Lee et al, 2010;Pons, 2008;Pons & Buelga, 2011) disregarded by direct care professionals with drug addicts, or influences by the positive experience of experimental use (Elzo, 2010;Londoño, 2010Moral & Ovejero, 2011; Ruiz-Juan y Ruiz-Risueño, 2011). The research carried out by Meneses et al (2010) on adolescence and risk situations in road safety also confirms differences by gender, reckless driving being more frequent in men than in women. The study by Gil and Romo (2008) on the Andalusian adolescent population also found results similar to those of our study regarding risk behaviors related to road safety, such as consumption of legal and illegal drugs, as well as differences by gender.…”
Section: Discussionmentioning
confidence: 56%
“…The human factor and norm transgression (Montoro, Alonso, Esteba, & Toledo, 2000;Montoro, Roca & Tortosa, 2008) are two variables influencing this accident rate. Authors such as Meneses, Gil, and Romo (2010) suggest that we continue analyzing motivations and perceptions of adolescents in relation to road safety; thus, the present study follows this recommendation, focusing on two common behaviors found during adolescence: drug use and reckless driving. Research-wise, we will study people's perceptions about different substances, whether myth or real, and their attitudes towards driving, riding, or being under the influence of substances.…”
Section: Extended Summarymentioning
confidence: 94%
“… 8 , 9 , 10 The program “Prevention of Trauma Related to Alcohol Use in Youth” PARTY is an initiative aimed at encouraging the youth between 14 and 18 years to attend activities in hospital to raise their awareness about the risks of driving under the influence of alcohol. 12 This study seeks to educate the population and improve their knowledge about the dangers exposed by not using safety equipment when driving or driving under intoxication. The response from the youth participating in the education model was rather favorable, as can be seen in the fact that before attending the session, 80% of the young people did not use any security element, while after the application the percentage of adolescents who did not use helmet decreased from 72% to 24%, driving a vehicle without a belt security from 65% to 20% and driving under intoxication from 49.3% to 8.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Por lo tanto, son varios los comportamientos de riesgos que tienen los jóvenes al volante y que les hacen tener tasas de accidentabilidad mayores que las de los conductores más maduros (Meneses et al, 2010).…”
Section: Personalidad Y Conducciónunclassified